Identification of compounds to promote diabetic wound healing based on transcriptome signature - Shang, Jiamin; Liu, Zhaoyu; Liang, Meidai; Yin, Zijie; Yang, Zeyu; Ye, Xiaomeng; Du, Guanhua; Yang, Xiuying (Frontiers in Pharmacology, 2025)
PurposeDiabetic wounds are characterized by delayed healing, and the resulting diabetic foot ulcer may lead to severe complications, including amputations and mortality. This study aimed to identify potential small molecule drug candidates that can enhance diabetic wound healing through integrating transcriptome signature and experimental validation strategies.MethodGene expression dataset (GSE147890) from a diabetic skin humanized mice model in the Gene Expression Omnibus database was analyzed to identify differentially expressed genes between diabetic and normal skin, as well as the wound edge at 24 h. The DEGs were integrated with wound-related genes from the Comparative Toxicogenomics Database to construct a diabetes-specific wound gene profile. Then, the expression signatures were analyzed using the ClusterProfiler package in R for Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Hub genes were identified through the String database and Cytoscope software. The Connectivity Map (CMap) was employed to predict compounds with potential therapeutic effects on diabetic wound healing. These predications were validated through in vitro and in vivo experiments.ResultsA total of 167 DEGs were identified between diabetic and normal wounds, with significant enrichment in biological processes related to the extracellular matrix and collagen. The top ten hub genes were predominantly associated with collagen synthesis and inflammatory responses. CMap analysis identified 12 small-molecule compounds, top four of which were further investigated. In vitro experiments demonstrated that two compounds promoted fibroblast proliferation. In vivo studies revealed that compound CG-930 enhanced early inflammatory responses and upregulated the Nod-like receptor signaling pathway, significantly improving wound healing in streptozotocin (STZ) -induced diabetic mice.ConclusionThis study highlights the altered expression profiles associated with delayed diabetic wound healing, including reduced inflammation and collagen production. Further drug screening identified compound CG-930 as a novel therapeutic agent with significant potential to promote wound healing in diabetic conditions.